2016
DOI: 10.33225/jbse/16.15.391
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Students’ Metacognitive Skills Through New Teaching Strategy (Group Investigation Integrated With Think Talk Write) in Biology Classroom

Abstract: Metacognitive skills play an important role in various students’ cognitive activities. Metacognitive skills can make the students become self-regulated learners. Metacognitive skills in biology teaching can be empowered through the implementation of the appropriate teaching strategies. This research was a quasi-experimental research designed to compare the effect of Group Investigation (GI) strategy, Think Talk Write (TTW), Group Investigation integrated with Think Talk Write (GITTW), and conventional teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
2
22
0
2
Order By: Relevance
“…Analysis of several previous studies reported that blended learning and PjBL were quite influential in improving students' creative thinking skills (Yustina et al, 2020), students' metacognitive behavior (Listiana et al, 2016), problem-solving abilities (Nawani et al, 2019), and generic science skills (Haviz et al, 2018). It also encourages creativity (Lucas, 2016) and positively correlates with teacher analysis skills (Aslan & Zhu, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of several previous studies reported that blended learning and PjBL were quite influential in improving students' creative thinking skills (Yustina et al, 2020), students' metacognitive behavior (Listiana et al, 2016), problem-solving abilities (Nawani et al, 2019), and generic science skills (Haviz et al, 2018). It also encourages creativity (Lucas, 2016) and positively correlates with teacher analysis skills (Aslan & Zhu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploring learning models is essential to improve thinking skills (Fitriani et al, 2019;Maryuningsih et al, 2019). The learning model must be designed appropriately to accustom students to think at higher levels (Listiana et al, 2016). Strengthening HOTS can be achieved when students actively understand and integrate knowledge with their experiences (Anderson & Krathwohl, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many previous studies have examined the 21 st century skills for prospective biology teachers in public universities. The writers found a number of previous studies that have studied about 21 st century skill for prospective biology teachers in public universities, such as critical thinking (Maryuningsih et al, 2019;Fitriani et al, 2019), metacognitive (Chang et al, 2020;Listiana et al, 2016), ICT (Aslan & Zhu, 2017), problem-solving (Nawani et al, 2019), generic science skill (Haviz et al, 2018), and creativity (Lucas, 2016). Maryuningsih et al (2019) conducted quasi-experimental research to investigate the level of critical thinking skills (CTS) of 37 PBTs through online genetic discussion forums, and the results of the research showed that the level of critical thinking skills of PBTs increased based on the nature of chromosome inheritance learning through online discussion forums.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al (2020) conducted a study of metacognitive inquiry activities to teach the central dogma concept of DNA replication and protein synthesis based on the metacognitive learning cycle (MLC) for students, and the results of this study showed that students' metacognition was expressed during the investigation process. Listiana et al (2016) conducted quasi-experimental research to compare the effect of group investigation (GI) strategy, think-talkwrite, group investigation integrated with think talk write and conventional method on the students' metacognitive skills empowerment in the biology classroom, and the results of the research showed that the implementation of teaching strategies had an effect to empower students' metacognitive skills.…”
Section: Introductionmentioning
confidence: 99%
“…This model can effectively encourage group collaboration in the inquiry process, encourage a better understanding of the topics they are studying. It also provides the amplest opportunity for students to determine what and how they will learn [27], become independent learners [28], and develop critical thinking skills [29], [30].…”
Section: Introductionmentioning
confidence: 99%